2020
DOI: 10.3390/children7090133
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Neurological Considerations in Neonates and Children

Abstract: The ongoing worldwide pandemic of the novel human coronavirus SARS-CoV-2 and the ensuing disease, COVID-19, has presented enormous and unprecedented challenges for all medical specialists. However, to date, children, especially neonates, have been relatively spared from the devastating consequences of this infection. Neurologic involvement is being increasingly recognized among adults with COVID-19, who can develop sensory deficits in smell and taste, delirium, encephalopathy, headaches, strokes, and periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 112 publications
1
81
0
6
Order By: Relevance
“…1 Many neurological manifestations of COVID-19 have been reported in the literature that range from mild non-specific features such as headache, lethargy or confusion; isolated focal signs including hyposmia, focal seizures, eye-movement abnormalities or ataxia; through to severe life-threatening conditions including status epilepticus, Guillain Barre syndrome, disseminated stroke syndromes and acute haemorrhagic necrotizing encephalopathy. 2,3 In addition to these, a newly recognized Kawasaki syndrome-like hyperinflammatory disorder has been recognized in children called as MIS-C. This presents with fever, laboratory evidence of inflammation and multisystem (> = 2 organ) involvement, manifesting up to 3-4 weeks following a mild or asymptomatic COVID-19 illness.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many neurological manifestations of COVID-19 have been reported in the literature that range from mild non-specific features such as headache, lethargy or confusion; isolated focal signs including hyposmia, focal seizures, eye-movement abnormalities or ataxia; through to severe life-threatening conditions including status epilepticus, Guillain Barre syndrome, disseminated stroke syndromes and acute haemorrhagic necrotizing encephalopathy. 2,3 In addition to these, a newly recognized Kawasaki syndrome-like hyperinflammatory disorder has been recognized in children called as MIS-C. This presents with fever, laboratory evidence of inflammation and multisystem (> = 2 organ) involvement, manifesting up to 3-4 weeks following a mild or asymptomatic COVID-19 illness.…”
Section: Discussionmentioning
confidence: 99%
“…Children are considered less susceptible to SARS-CoV-2 compared with adults [ 131 ] and generally present with milder COVID-19 symptoms [ 132 ]. While neurological manifestations are relatively rare among children, gustatory dysfunction has been increasingly reported in younger cohorts [ 133 ]. Fontanet et al [ 134 ] conducted a retrospective cohort study of primary school pupils aged six to 11 years in northern France and found that ageusia is present in only 1% of them.…”
Section: Gustatory Dysfunctionmentioning
confidence: 99%
“…oronaviruses primarily cause respiratory disease; however, severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus, and newly identified SARS-CoV-2 have been associated with a range of disorders of the peripheral and central nervous system (CNS). [1][2][3][4][5][6][7][8][9] Early reports from Wuhan, China, described a spectrum of neurologic conditions associated with SARS-CoV-2 infection in 36% of 214 adults hospitalized with coronavirus disease 2019 (COVID-19). 10 Reported neurologic and psychiatric symptoms in adult patients with COVID-19 include anosmia/ageusia, 11,12 headaches, 13 dizziness/ataxia, 10 psychosis, dementia, depression, anxiety, and mania.…”
mentioning
confidence: 99%